Surface characterization and mechanical behavior of aluminum based metal matrix composite reinforced with nano Al2O3, SiC, TiO2 particles - Shuvho, M.B.A.; Chowdhury, M.A.; Kchaou, M.; Roy, B.K.; Rahman, A.; Islam, M.A. (Chemical Data Collections, 2020)
Aluminum based metal matrix composites (AMMCs) have the potential for replacing conventional monolithic materials due to excellent fatigue, creep and wear resistance, high temperature retention, and high strength to weight ratio. Thus Aluminum based metal matrix composites have several applications in different industries including Aerospace and Automotive. This study revealed that Al 6063 based metal matrix composites reinforced with Al2O3, SiC, TiO2 have higher hardness, tensile strength, and yield strength as compared to the pure Al 6063. This study shows that hardness, tensile strength, and yield strength are increasing as increasing SiC particles content. Microstructure and surface morphological studies have been carried out to see their surface and particles distribution. Energy Dispersive X-ray Spectroscopy (EDS) and XRD analysis have been conducted to identify elements content. Fourier Transform Infrared Spectroscopy (FTIR) analysis is carried out to identify chemical functional group of the Al6063 metal matrix composites.